Przestrzenie polskiej imigracji w Holandii po 2004 roku: Polenhotels - Kruk, Ewa (Studia Etnologiczne i Antropologiczne, 2013)
A conclusion deriving from an attempt at “inscribing” the phenomenon of immigration into a local space, is the existence of an inseparable relationship between them. Territory segregation is used as a tool levelling social tension against an ethnic background. Immigrants usually inhabit postindustrial, and poor districts offering low standard flats in the local structure. In the case of the Polish immigrants in Holland, it is reflected in the phenomenon called Polenhotels, namely housing estates created on the basis of former monasteries, institutions for the handicapped or army storehouses where they are accommodated. Ghettoization locates particular groups of people (not only in a physical, but also discursive dimension) in a marginal position.